Cyberbullying in Kenyan universities: Lessons and insights from the personal experience of deans of students - Angela Kogos; TOM KWANYA; Lucy Kibe; Erick Ogolla; Claudior Onsare (Journal of Student Affairs in Africa)
Deans of students are the main points of contact between the university management and the students they serve in Kenyan universities. This position exposes them to acts of hostility both online and offline. This article explores the experiences of deans of students in Kenyan universities with cyberbullying. It specifically analyses the prevalence of cyberbullying among deans of students in Kenyan universities, the nature of cyberbullying meted out to deans of students, the strategies used by the deans to counter cyberbullying, and the effectiveness of these strategies in mitigating cyberbullying. This study was qualitative. Data was collected through interviews with 25 deans of students from eight private and seventeen public universities in Kenya. The study findings show that most of the deans of students have been bullied online at some time or another by their students. Deans of students were bullied for their looks, competencies, and associations. This, in turn, has affected how they perform their duties. The deans countered cyberbullying by blocking the bullying accounts, unfriending hostile “friends”, deactivating or disengaging from social media, seeking legal redress, creating rapport with the students to stem hostility, seeking counselling, or confronting the bullies directly. The study revealed that the strategies used by the deans of students to curb cyberbullying were largely ineffective. This study recommends that universities provide staff sensitization training on cyberbullying and strengthen counselling and peer support systems among staff. This would enable their staff, such as deans of students, to deal with the effects of cyberbullying. These recommendations, if implemented, could help secure a favourable online working environment for the deans of students at Kenyan universities as they interact with their students, increase their morale at work, and improve the working relationship between students and the deans of students.